Multiplex single-cell visualization of nucleic acids and protein during HIV infection. Issue 1 (December 2017) - Puray-Chavez, Maritza; Tedbury, Philip; Huber, Andrew; Ukah, Obiaara; Yapo, Vincent; Liu, Dandan; Ji, Juan; Wolf, Jennifer; Engelman, Alan; Sarafianos, Stefan
Abstract Technical limitations in simultaneous microscopic visualization of RNA, DNA, and proteins of HIV have curtailed progress in this field. To address this need we develop a microscopy approach, multiplex immunofluorescent cell-based detection of DNA, RNA and Protein (MICDDRP), which is based on branched DNA in situ hybridization technology. MICDDRP enables simultaneous single-cell visualization of HIV (a) spliced and unspliced RNA, (b) cytoplasmic and nuclear DNA, and (c) Gag. We use MICDDRP to visualize incoming capsid cores containing RNA and/or nascent DNA and follow reverse transcription kinetics. We also report transcriptional "bursts" of nascent RNA from integrated proviral DNA, and concomitant HIV-1, HIV-2 transcription in co-infected cells. MICDDRP can be used to simultaneously detect multiple viral nucleic acid intermediates, characterize the effects of host factors or drugs on steps of the HIV life cycle, or its reactivation from the latent state, thus facilitating the development of antivirals and latency reactivating agents. Technical limitations in simultaneous microscopic visualization of HIV transcription from individual integration sites have curtailed progress in the field. Here the authors report a branched DNA in situ hybridization method for direct single-cell visualization of HIV DNA, RNA, and protein.